2022
DOI: 10.1212/wnl.0000000000200058
|View full text |Cite
|
Sign up to set email alerts
|

Measures Associated With Early, Late, and Persistent Clinically Significant Symptoms of Depression 1 Year After Stroke in the AFFINITY Trial

Abstract: Objective:To determine the sociodemographic and clinical factors associated with early, late and persistent clinically significant symptoms of depression during the first year after a stroke.Methods:Cohort study of 1221 men and women recruited within two weeks of stroke onset in Australia, New Zealand and Vietnam. The NIH Stroke Scale (NIHSS) was used to assess the severity of the stroke. Other study measures included age, sex, marital status, living arrangements, function before the stroke, depression before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…The literature on factors influencing optimism is sparse, but studies of poststroke depression identify that the factors most associated with the development of poststroke depression are older age, stroke severity, and preexisting diagnosis of depression. 26 In evaluation of comorbidities and medical complications in this sample, there were no significant differences among groups in the total number or individual type of comorbidities and medical complications, but this interplay between mood, affect, and comorbidities in stroke may benefit from exploration in a larger data set.…”
Section: Discussionmentioning
confidence: 81%
“…The literature on factors influencing optimism is sparse, but studies of poststroke depression identify that the factors most associated with the development of poststroke depression are older age, stroke severity, and preexisting diagnosis of depression. 26 In evaluation of comorbidities and medical complications in this sample, there were no significant differences among groups in the total number or individual type of comorbidities and medical complications, but this interplay between mood, affect, and comorbidities in stroke may benefit from exploration in a larger data set.…”
Section: Discussionmentioning
confidence: 81%
“…An increased awareness of the interplay between prestroke depressive symptoms and differential functional outcomes poststroke is important when considering targeted interventions to enhance strategies for encouraging participation in poststroke rehabilitation. Antidepressant usage poststroke has not been demonstrated to benefit poststroke functional recovery, 35,36 even in secondary analysis of those with clinical depression, 37 and has the potential for harm, 32,36 so it should not be encouraged routinely. We would suggest that alternative clinical trial approaches such as targeting patients with recent depressive symptoms are needed to see if this can improve poststroke outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Existing systematic reviews suggest that one in three stroke survivors will experience clinically significant symptoms of depression, and that the proportion of those affected does not vary much with time [4 ▪ ]. In contrast, the results of the Assessment of Fluoxetine in Stroke Recovery (AFFINITY) trial found that about 19% of 1221 participants showed evidence of clinically significant symptoms of depression at the time of recruitment 2–15 days after a mild to moderate acute stroke (either ischaemic or haemorrhagic) [5 ▪▪ ]. The study defined clinically significant symptoms of depression as a score of 9 or greater on the Patient Health Questionnaire (PHQ-9).…”
Section: Stroke and Depressionmentioning
confidence: 96%
“…The study defined clinically significant symptoms of depression as a score of 9 or greater on the Patient Health Questionnaire (PHQ-9). In addition, the proportion of those affected by clinically significant symptoms of depression decreased progressively with time to about 10% after 3 months and 8% after 6 months [5 ▪▪ ]. The results of AFFINITY also showed that although the proportion of people affected by depression decreases with time, one in three survivors experienced clinically significant symptoms at some point over a period of 12 months, and in 30% of these symptoms were present both during the sub-acute (≤ 3 months) and recovery phases (3–12 months) [6 ▪ ].…”
Section: Stroke and Depressionmentioning
confidence: 96%